Digital representation of engagement:: towards a perception of commitment through symbolic actions - Ballesteros Herencia, Carlos A. (2019)
Engagement has received a growing study within the Social Sciences until becoming the mainstream of public communication. The digital environments make possible to study their manifestation through symbolic behavior, publicly recorded, in the form of "Like", Share or Comment messages. However, it has been pointed out that its definition is in a state of refinement, so a synthesis was made based on a multidisciplinary state of issue, as well as a quantification of its evolution in the last 30 years, finding an increase of 1300 % in its academic use. Despite the great potential for interaction generated by the engagement, this process remains constrained to a traditional use in which social network administrators prefer to keep the information under control.